CoSi2 alloy toughened high-entropy carbide composite ceramic as well as preparation method and application thereof

By introducing CoSi2 alloy into high entropy carbide ceramics and adopting SPS sintering process, the problems of high entropy carbide ceramics are solved, and the combination of low-temperature densification and high hardness are achieved.

CN119775010AActive Publication Date: 2025-04-08GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411870818.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Due to the high sintering temperature and poor fracture toughness, high entropy carbide ceramics limit their industrial applications, especially while maintaining high hardness, it is difficult to achieve low temperature densification and fracture toughness improvement.

Method used

CoSi2 alloy is used as the liquid phase sintering aid. Through the SPS sintering process, the solid solution process of (Ti, Zr, Nb, Ta, Mo)C high-entropy ceramics is promoted, and a low-melting liquid phase is formed during the sintering process to achieve low temperature densification.

Benefits of technology

It significantly improves the fracture toughness of high-entropy carbide ceramics, while maintaining their high hardness characteristics, reducing sintering temperature and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775010A_ABST
    Figure CN119775010A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite ceramics, and discloses a CoSi2 alloy toughened high-entropy carbide composite ceramic as well as a preparation method and application thereof. The composite ceramic is (Ti0. 2Zr0. 2Nb0. 2Ta0. 2Mo0. 2) C-CoSi2, and is prepared by the following steps: mixing TiO2 powder, ZrO2 powder, Nb2O5 powder, Ta2O5 powder, MoO3 powder and carbon powder to obtain mixed powder, adding the mixed powder into absolute ethyl alcohol, stirring to obtain slurry, carrying out ball milling, drying and sieving, carrying out dry pressing to obtain a green body, sintering at 1000-1600 DEG C in a protective atmosphere, mixing the prepared high-entropy powder and CoSi2 powder, carrying out ball milling, drying and sieving, and carrying out dry pressing to obtain a green body; the composite ceramic is prepared through SPS sintering under the uniaxial pressure of 25-30 MPa and at the temperature of 1500-1700 DEG C. The composite ceramic has the advantages of high density, high hardness, high fracture toughness and the like, and can be applied to the field of preparation of materials difficult to cut.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite ceramics, and more specifically, relates to a CoSi 2 Alloy-toughened high-entropy carbide composite ceramics, preparation method and application thereof. Background Art

[0002] Compared with traditional mono- or binary transition metal carbide ceramics, high entropy carbide ceramics have higher hardness (~24GPa), wear resistance and stability at high temperatures due to their unique high entropy effect, making them ideal for making high-performance cutting tools, wear-resistant parts and other demanding applications in the fields of aviation, military and energy. However, due to the characteristics of strong covalent bonds, low self-diffusion coefficients and severe lattice distortion, high entropy carbide ceramics have the problems of high sintering temperature and poor fracture toughness, which greatly limits their industrial applications.

[0003] Previous literature studies have shown that the use of low-melting-point metal liquid phase sintering can effectively reduce the densification temperature of high-entropy carbide ceramics and improve the fracture toughness, but it significantly sacrifices the high hardness advantage of high-entropy carbide ceramics. For example, (Hf-Ta-Ti-Nb-V)C and (Ti-V-Nb-Ta-W)C ceramics can be densified by adding 19.2 vol.% metal Co and 12 vol.% metal Ni, respectively, at 1400 ° C. The fracture toughness of (Hf-Ta-Ti-Nb-V)C-19.2 vol.% Co and (TV-Nb-Ta-W)C-12 vol.% Ni ceramics can reach 8.5 MPa·m 1 / 2 and 6.7MPa·m 1 / 2 , but their Vickers hardness values ​​are low, only 14.0GPa and 14.3GPa respectively. The residual low-hardness metal phase in the ceramic matrix after sintering is the main reason for the decrease in hardness of high-entropy carbide ceramics. Therefore, it is urgent to solve the problem of how to maintain its inherent high hardness characteristics while achieving low-temperature densification and improvement of fracture toughness of high-entropy carbide ceramics. Summary of the invention

[0004] In order to solve the above-mentioned shortcomings and disadvantages of the prior art, the primary purpose of the present invention is to provide a CoSi 2 Alloy-toughened high-entropy carbide composite ceramics.

[0005] Another object of the present invention is to provide CoSi 2 A method for preparing alloy toughened high entropy carbide composite ceramics. The method introduces CoSi 2As a liquid phase sintering aid, it significantly improves the fracture toughness of (Ti, Zr, Nb, Ta, Mo)C high entropy ceramics while achieving low-temperature densification of ceramics and maintaining the high hardness of high entropy carbide ceramics.

[0006] Another object of the present invention is to provide the CoSi 2 Application of alloy-toughened high-entropy carbide composite ceramics.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A CoSi 2 Alloy toughened high entropy carbide composite ceramics are (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C-CoSi 2 , is to mix TiO 2 Powder, ZrO 2 Powder, Nb 2 O 5 Pink, Ta 2 O 5 Powder, MoO 3 The powder and carbon powder are mixed to obtain a mixed powder, which is added into anhydrous ethanol and stirred to obtain a slurry, which is ball-milled, dried, sieved, and then dry-pressed into a green body A. The green body A is sintered at 1500-1600°C under a protective atmosphere to obtain (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder; the high entropy powder and CoSi 2 The powders are mixed, anhydrous ethanol is added for ultrasonic stirring to obtain a slurry, which is then ball-milled, dried, sieved, and dry-pressed into a green body B; the green body B is sintered at 1500-1700° C. under a uniaxial pressure of 25-30 MPa by SPS.

[0009] Preferably, the Vickers hardness of the composite ceramic is 24.7 to 26 GPa, and the fracture toughness is 5 to 5.5 MPa·m 1 / 2 .

[0010] Preferably, the TiO 2 Powder, ZrO 2 Powder, Nb 2 O 5 Pink, Ta 2 O 5 Powder, MoO 3The particle size of the powder is 1 to 2 μm; the particle size of the carbon powder is 100 nm to 1 μm. 2 The particle size of the powder is 0.4 to 0.6 μm.

[0011] Preferably, the (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder and CoSi 2 The volume ratio of the powder is (90~97.5):(2.5~10).

[0012] The CoSi 2 The preparation method of alloy toughened high entropy carbide composite ceramic comprises the following steps:

[0013] S1. TiO 2 Powder, ZrO 2 Powder, Nb 2 O 5 Pink, Ta 2 O 5 Powder, MoO 3 Mix the powder and carbon powder to obtain a mixed powder;

[0014] S2. Add the mixed powder into anhydrous ethanol and stir ultrasonically to prepare a slurry, then add Si 3 N 4 The medium ball is ball-milled, dried, sieved and dry-pressed into a green body, which is sintered at 1000-1600°C under a protective atmosphere to obtain (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder;

[0015] S3. 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder and CoSi 2 The powder is mixed, anhydrous ethanol is added and ultrasonically stirred to obtain a slurry, and then silicon nitride medium balls are added, ball milled, dried, sieved, and then dry-pressed into a green body;

[0016] S4. Under a uniaxial pressure of 25 to 30 MPa, the green body is sintered at 1500 to 1700 ° C by SPS and kept warm to obtain CoSi 2 Alloy toughened high entropy carbide composite ceramic, its molecular formula (Ti 0.2 Zr 0.2 Nb0.2 Ta 0.2 Mo 0.2 )C-CoSi 2 .

[0017] Preferably, in step S2, the rotation speed of the ball mill is 100-300 r / min, and the ball milling time is 18-36 h; the drying temperature is 60-80° C., and the drying time is 12-24 h.

[0018] Preferably, the heat treatment procedure of the pressureless sintering in step S2 is: first increase the temperature to 50-1000°C at a rate of 15-20°C / min, start filling with nitrogen to 1 atmosphere, and continue to increase the temperature to 1500-1600°C at a rate of 8-10°C / min; after the temperature increase procedure is completed, keep the temperature for 0.5-1h, then cool down to 710-810°C at a rate of 8-15°C / min and then cool down with the furnace.

[0019] Preferably, the rotation speed of the ball mill in step S3 is 100-200 r / min, and the ball milling time is 18-36 h; the drying temperature is 60-80° C., and the drying time is 16-24 h.

[0020] Preferably, the SPS sintering process described in step S4 is: firstly heating to 1500-1700°C at a rate of 80-100°C / min, keeping the temperature for 10-15min, and symmetrically cooling down below 710-800°C with the furnace.

[0021] The CoSi 2 Application of alloy-toughened high-entropy carbide composite ceramics in the preparation of difficult-to-cut ceramics.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts a pressureless heat treatment process, which is simple, low-cost and energy-saving.

[0024] 2. The present invention uses CoSi 2 The alloy is a binder. Through the SPS sintering process, it can promote the solid solution process of (Ti, Zr, Nb, Ta, Mo) C, and form a low melting point liquid phase during the sintering process, which can promote the low-temperature densification process. It has a fast sintering speed, reduces the sintering temperature, and is energy-saving and environmentally friendly.

[0025] 3. The high entropy carbide composite ceramics prepared by the present invention improve fracture toughness while maintaining high hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 CoSi prepared in Examples 1 to 3 2SEM photographs of the cross-sections of the alloy-toughened high-entropy carbide composite ceramic and the high-entropy carbide ceramic of Comparative Example 1. DETAILED DESCRIPTION

[0027] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0028] TiO used in the present invention 2 Powder, ZrO 2 Powder, Nb 2 O 5 Pink, Ta 2 O 5 Powder and MoO 3 The particle size of the powder is 1-2 μm; the particle size of the carbon powder is 100 nm-1 μm, and the particle size of the CoSi 2 The particle size of the powder is 0.4 to 0.6 μm.

[0029] Example 1

[0030] 1. Mix TiO 2 、ZrO 2 , Nb 2 O 5 、 2 O 5 、MoO 3 The powder and the carbon powder are mixed to obtain a mixed powder;

[0031] 2. Add anhydrous ethanol to the mixed powder, stir ultrasonically to obtain a slurry, then add silicon nitride medium balls and grind them in a roller ball mill. After drying and sieving, put them into an iron mold and dry-press them into a green billet;

[0032] 3. The green billet was heated to 1000°C at a rate of 20°C / min, and nitrogen was filled to 1 atmosphere. The temperature was then raised to 1600°C at a rate of 10°C / min and kept at that temperature for 1 hour. The temperature was then lowered to 800°C at a rate of 10°C / min and then cooled with the furnace. After being crushed by a high-speed crusher and passed through a 100-mesh sieve, (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder.

[0033] 4. Add (Ti) with a volume ratio of 9:1 0.2 Zr 0.2 Nb 0.2 Ta0.2 Mo 0.2 )C high entropy powder and CoSi 2 The powders are mixed, anhydrous ethanol is added for ultrasonic stirring to obtain a slurry, which is then ball-milled in a roller mill, dried, sieved, loaded into an iron mold, and dry-pressed into a green body;

[0034] 5. The green body was heated to 1600℃ at a rate of 100℃ / min under a uniaxial pressure of 30MPa for SPS sintering and kept at this temperature for 10min, and then cooled symmetrically below 600℃ with the furnace to obtain CoSi 2 Alloy toughened high entropy carbide composite ceramic, its molecular formula is (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C-CoSi 2 .

[0035] Example 2

[0036] 1. Mix TiO 2 、ZrO 2 , Nb 2 O 5 、 2 O 5 、MoO 3 The powder and the carbon powder are mixed to obtain a mixed powder;

[0037] 2. Add the mixed powder to anhydrous ethanol and stir ultrasonically to obtain a slurry, then add silicon nitride medium balls and grind them in a roller ball mill. After drying and sieving, put them into an iron mold and dry-press them into a green billet;

[0038] 3. The blank was heated to 1000°C at a rate of 20°C / min, and nitrogen was filled to 1 atmosphere. The blank was heated to 1600°C at a rate of 10°C / min and kept at that temperature for 1 hour. The blank was then cooled to 800°C at a rate of 10°C / min and cooled with the furnace. After being crushed by a high-speed crusher and passed through a 100-mesh sieve, (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder.

[0039] 4. The volume ratio of 97.5:2.5 (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder and CoSi 2The powders are mixed and anhydrous ethanol is added for ultrasonic stirring to obtain a slurry; then silicon nitride medium balls are added and milled in a roller ball mill, and after drying and sieving, they are loaded into an iron mold and dry-pressed into a green body;

[0040] 5. The green body was heated to 1600℃ at a rate of 100℃ / min under a uniaxial pressure of 30MPa for SPS sintering and kept at this temperature for 10min, and then cooled symmetrically below 800℃ with the furnace to obtain CoSi 2 Alloy toughened high entropy carbide composite ceramic, its molecular formula is (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C-CoSi 2 .

[0041] Example 3

[0042] 1. Mix TiO 2 Powder, ZrO 2 Powder, Nb 2 O 5 Pink, Ta 2 O 5 Powder, MoO 3 Mix the powder and the carbon powder to obtain a mixed powder;

[0043] 2. Add the mixed powder to anhydrous ethanol and stir ultrasonically to obtain a slurry, then add silicon nitride medium balls and grind them in a roller ball mill. After drying and sieving, put them into an iron mold and dry-press them into a green billet;

[0044] 3. The green billet was heated to 1000°C at a rate of 20°C / min, and nitrogen was filled to 1 atmosphere. The temperature was then raised to 1600°C at a rate of 10°C / min and kept at that temperature for 1 hour. The temperature was then lowered to 800°C at a rate of 10°C / min and then cooled with the furnace. After being crushed by a high-speed crusher and passed through a 100-mesh sieve, (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder.

[0045] 4. The volume ratio of 95:5 (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder and CoSi 2 The powder is mixed, anhydrous ethanol is added for ultrasonic stirring to obtain a slurry, and then silicon nitride medium balls are added, and the slurry is milled by a roller ball mill. After drying and sieving, the slurry is loaded into an iron mold and dry-pressed into a green body.

[0046] 5. The green body was heated to 1600℃ at a rate of 100℃ / min for SPS sintering under a uniaxial pressure of 10MPa and kept at this temperature for 10min, and then cooled symmetrically below 800℃ with the furnace to obtain CoSi 2 Alloy toughened high entropy carbide composite ceramic, its molecular formula is (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C-CoSi 2 .

[0047] Comparative Example 1

[0048] 1. Mix TiO 2 Powder, ZrO 2 Powder, Nb 2 O 5 Pink, Ta 2 O 5 Powder, MoO 3 Mix the powder and the carbon powder to obtain a mixed powder;

[0049] 2. Add the mixed powder to anhydrous ethanol and stir ultrasonically to obtain a slurry, then add silicon nitride medium balls and grind them in a roller ball mill. After drying and sieving, put them into an iron mold and dry-press them into a green billet;

[0050] 3. The green billet was heated to 1000°C at a rate of 20°C / min, and nitrogen was filled to 1 atmosphere. The temperature was then raised to 1600°C at a rate of 10°C / min and kept at that temperature for 1 hour. The temperature was then lowered to 710-810°C at a rate of 10°C / min and then cooled with the furnace. After being crushed by a high-speed crusher and passed through a 100-mesh sieve, (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder.

[0051] 4. 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 ) C high entropy powder is added to anhydrous ethanol and ultrasonically stirred to obtain a slurry, and then silicon nitride medium balls are added to the slurry and milled by a roller ball mill. After drying and sieving, the slurry is loaded into an iron mold and dry-pressed into a green body;

[0052] 5. The green body was heated to 1600℃ at a rate of 100℃ / min for SPS sintering under a uniaxial pressure of 10MPa and kept at this temperature for 10min, and then cooled symmetrically below 800℃ with the furnace to obtain a high entropy carbide ceramic with the molecular formula (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C.

[0053] Figure 1 CoSi prepared in Examples 1 to 3 2 SEM photos of the cross-section of the alloy toughened high entropy carbide composite ceramic and the high entropy carbide ceramic of Comparative Example 1. (a) is the high entropy carbide ceramic of Comparative Example 1. (b) is the CoSi 2 Alloy toughened high entropy carbide composite ceramic, (c) is CoSi of Example 3 2 Alloy toughened high entropy carbide composite ceramic, (d) is CoSi of Example 1 2 High entropy carbide composite ceramics. Figure 1 It can be seen that the CoSi 2 The fracture mode of alloy toughened high entropy carbide composite ceramics is intergranular fracture, while the cross section of high entropy carbide shows a fracture mode dominated by intergranular fracture. At the same time, "housings" can be observed in the area indicated by the green dotted line, which is the main feature of grain pullout, indicating that grain pullout is the main toughening mechanism of ceramics. In addition, there are some large-sized grains ((Co 3 Mo 3 )C phase), and most of them are transgranular fractures with smooth cross sections, which weakens the fracture toughness of the material. Its fracture toughness is 3.47±0.26MPa·m 1 / 2 . CoSi of Example 2 2 The alloy-toughened high-entropy carbide composite ceramic has a porous structure, and the pore size is comparable to the grain size, which seriously damages the mechanical properties of the material. The fracture toughness of this sample is the lowest, which is 2.81±0.21MPa·m 1 / 2 Example 3 CoSi 2 The fracture form of alloy toughened high entropy carbide composite ceramics is also intergranular fracture, and many "housings" can be observed, which is the main feature of grain pullout, indicating that grain pullout is the main toughening mechanism of ceramics and there are no large-sized grains. Its fracture toughness is 5.23±0.24MPa·m 1 / 2 , relative density is 100%, and Vickers hardness is 25±0.27GPa.

[0054] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A composite ceramic of CoSi2 alloy toughened high entropy carbide, characterized in that: The composite ceramic is (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C-CoSi2 is prepared by mixing TiO2 powder, ZrO2 powder, Nb2O5 powder, Ta2O5 powder, MoO3 powder and carbon powder in a molar ratio of 1:1:0.5:0.5:1:17 to obtain a mixed powder, adding anhydrous ethanol to stir to obtain a slurry, and then ball milling, drying, sieving and dry pressing to form a blank A, and sintering the blank A at 1000-1600°C under a protective atmosphere to obtain (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder; mixing the high entropy powder and CoSi2 powder, adding anhydrous ethanol and ultrasonically stirring to obtain a slurry, and then ball milling, drying, sieving and dry pressing into a green body B; under a uniaxial pressure of 25 to 30 MPa, the green body B is sintered at 1500 to 1700°C by SPS.

2. The CoSi2 alloy toughened high entropy carbide composite ceramic according to claim 1, characterized in that: The composite ceramic has a Vickers hardness of 24.7 to 26 GPa and a fracture toughness of 5 to 5.5 MPa·m 1 / 2 .

3. The CoSi2 alloy toughened high entropy carbide composite ceramic according to claim 1, characterized in that: The particle sizes of the TiO2 powder, ZrO2 powder, Nb2O5 powder, Ta2O5 powder and MoO3 powder are all 1-2 μm; the particle size of the carbon powder is 100 nm-1 μm, and the particle size of the CoSi2 powder is 0.4-0.6 μm.

4. The CoSi2 alloy toughened high entropy carbide composite ceramic according to claim 1, characterized in that: The 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )The volume ratio of C high entropy powder and CoSi2 powder is (90~97.5):(2.5~10).

5. The method for preparing the composite ceramic of CoSi2 alloy toughened high entropy carbide according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. TiO2 powder, ZrO2 powder, Nb2O5 powder, Ta2O5 powder, MoO3 powder and carbon powder were mixed in a molar ratio of 1:1:0.5:0.5:1:17 to obtain a mixed powder; S2. The mixed powder is added to anhydrous ethanol and ultrasonically stirred to obtain a slurry, and then Si3N4 medium balls are added for ball milling, dried, sieved, and dry pressed into a green body. The green body is sintered at 1500-1600°C under a protective atmosphere to obtain (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C high entropy powder; S3. 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 ) C high entropy powder and CoSi2 powder are mixed, anhydrous ethanol is added and ultrasonically stirred to prepare a slurry, and then silicon nitride medium balls are added, ball milled, dried, sieved, and then dry-pressed into a green body; S4. Under a uniaxial pressure of 25 to 30 MPa, the green body is sintered at 1500 to 1700 ° C by SPS and kept warm to obtain a composite ceramic of CoSi2 alloy toughened high entropy carbide, whose molecular formula (Ti 0.2 Zr 0.2 Nb 0.2 Ta 0.2 Mo 0.2 )C-CoSi2.

6. The method for preparing the composite ceramic of CoSi2 alloy toughened high entropy carbide according to claim 5, characterized in that: The rotation speed of the ball mill in step S2 is 100-300 r / min; the ball milling time is 18-36 h; the drying temperature is 60-80° C., and the drying time is 12-24 h.

7. The method for preparing the composite ceramic of CoSi2 alloy toughened high entropy carbide according to claim 5, characterized in that: The heat treatment procedure of the pressureless sintering in step S2 is: first, heat up to 50-1000°C at a rate of 15-20°C / min, start filling with nitrogen to 1 atmosphere, and then heat up to 1500-1600°C at a rate of 8-10°C / min; after the heating procedure is completed, keep warm for 0.5-1h, then cool down to 710-810°C at a rate of 8-15°C / min and then cool down with the furnace.

8. The method for preparing the composite ceramic of CoSi2 alloy toughened high entropy carbide according to claim 5, characterized in that: In step S3, the rotation speed of the ball mill is 100-200 r / min, and the ball milling time is 18-36 h; the drying temperature is 60-80° C., and the drying time is 16-24 h.

9. The method for preparing the composite ceramic of high CoSi2 alloy toughened high entropy carbide according to claim 5, characterized in that: The SPS sintering process described in step S4 is: firstly heat up to 1500-1700°C at a rate of 80-100°C / min, keep warm for 10-15min, and then cool down symmetrically to below 710-800°C with the furnace.

10. Use of the composite ceramic of CoSi2 alloy toughened high entropy carbide according to any one of claims 1 to 4 in the preparation of difficult-to-cut ceramics.

Citation Information

Patent Citations

  • High-entropy ceramic with fine grains, high hardness and high toughness as well as preparation method and application of high-entropy ceramic

    CN115557793A

  • Whisker toughened high-entropy carbide composite ceramic as well as preparation method and application thereof

    CN116178034A

  • Preparation method of silicon nitride ceramic substrate with high toughness, high strength and high thermal conductivity

    CN116768637A

  • Ultra-hard composite material and method for manufacturing the same

    US20090074604A1

  • Environmental barrier coating

    US20220065113A1

Cited By

  • High-toughness silicon nitride ceramic substrate and preparation method thereof

    CN121494579A